Total body irradiation and allogeneic bone marrow transplantation – Sofia University Hospital experience - Gocheva, Lilia; Sergieva, Katja (Contemporary Oncology/Współczesna Onkologia, 2009)
Aim of the study: To report the long-term outcome in patients with leukaemias, who had conditioning regimens including total body irradiation (TBI) prior to bone marrow transplantation (BMT), and to establish independent factors correlated with treatment outcome. Material and methods: Between January 2002 and December 2007, 18 patients, 11 males and 7 females with median age of 12 years (range 8-50), received TBI. Initial diagnoses were acute lymphoblastic leukaemia (ALL) 11 (61%), acute myeloid leukaemia (AML) 4 (22%), and chronic myeloid leukaemia (CML) 3 (17%). Pre-transplantation disease status was defined as remission 11 (61%), progression 4 (22%), and chronic phase 3 (17%). All the patients were conditioned with a high-dose chemoradiotherapy regimen including fractionated TBI delivering 10 to 12 Gy in 15 (73%) and a single fraction of 2 Gy in 3 (17%) of the cases. TBI was performed in alternate prone and supine positions with a 60 Co machine. In 13 (72%) patients transplantation was carried out from an HLA-identical related donor and in 5 (28%) from an unrelated donor. Seventeen allogeneic transplantations were of peripheral blood stem cells and 1 was of bone marrow stem cells. Post-transplantation clinical, biological, and functional evaluations were performed on days 30, 100, 180, at 1 year, and annually thereafter. Each evaluation included an assessment of the study end points: marrow chimerism, disease status (complete remission or relapse), survival status (alive or dead), treatment-related toxicity (TRT), treatment-related mortality (TRM) and graft- versus -host-disease (GvHD). Results: Median follow-up from BMT was 27 months (range 3-52). Sixteen patients achieved engraftment, 2 patients had primary graft failure. Seven of 18 (39%) evaluable patients developed acute GvHD, 6 (35%) patients developed chronic GvHD. At the time of reporting 9 of 18 patients remain alive and in remission. Nine patients died, 4 (22%) because of relapse and 5 (28%) because of TRM. The cause of TRM was acute GvHD (2) and fatal – hepatic toxicity (1), neurological toxicity (1) and idiopathic pneumonia syndrome (1). The Kaplan-Meier estimates of 1- and 3-year overall survival (OS) for patients were 58%:31%, respectively. In univariate analysis, no differences were observed regarding age, gender, initial diagnosis, status of the disease, total dose of TBI, HLA-identity, and effect of acute GvHD. Chronic GvHD was associated with increased OS (p = 0.05). Conclusion: The achieved 3-year OS and TRM are comparable to those cited in the reference literature. The develop-ment of chronic GvHD exerted a signi-ficant impact on the estimated OS. However, the small number of cases precludes a definitive conclusion on the efficacy of the regimens used and further evaluation is required.